The Effect of Economic Literacy, Peer Groups, and Parents Socioeconomic Status Towards Students’ Consumption Behavior - Muslimin, Fatkhul; Hanum, Farida; Septia, Alifurriza Qurnia (Fakultas Ekonomi, Universitas Negeri Semarang, 2020)
The purpose of this study was to explain the effect of economic literacy towards students’ consumption behavior, effect of peer groups towards students’ consumption behavior and effect of parents sosioeconomic status toward students’ consumption behavior. The research location was conducted in SMAN Selong City, East Lombok, NTB. This research uses a quantitative approach because the research data using statistics and SPSS. The population in this study amounted to 308, and the study sample consisted of 174 students taken by proportional area random sampling. Data on research results obtained through questionnaires and tests, data analysis techniques using quantitative descriptive, testing requirements analysis, and testing hypotheses. The results of this study show that there is positive and significant effect of economic literacy towards students’ consumption behavior, there is positive and significant effect of peer groups towards students’ consumption behavior, and there is significant effect on parents' socioeconomic status towards students’ consumption behavior. The conclusion of this study states that there is a positive and significant influence of the variables of economic literacy, peer groups, and parents sosioeconomic status towards students’ consumption behavior.